Antifungal activity of chitosan against Alternaria alternata and Colletotrichum gloeosporioides - Živković, Svetlana; Stevanović, Miloš; Đurović, Sanja; Ristić, Danijela; Stošić, Stefan (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2018)
Chitosan and its derivatives have been reported as a promising alternative for control ofpostharvest fungal pathogens. The objective of this study was to evaluate in vitro and in situ antifungal activity of chitosan against Alternaria alternata and Colletotrichum gloeosporioides isolated from decayed apple fruits. The fungi were tested in vitro using PDA medium with three concentrations of chitosan (1, 2 and 3 mg/ml). Fungal growth of the test pathogens was significantly affected by all chitosan doses (P
Keywords: Chitosan; Antifungal activity; Postharvest pathogens; Apple fruits